FEATURES OF DESIGN OF TIED-ARCH BRIDGES WITH FLEXIBLE INCLINED SUSPENSION HANGERS - Samosvat, V. O.; Rongling, Zhang; Hololobova, O. O.; Buriak, S. Y. (Science and Transport Progress, 2017)
Purpose. Investigation and analysis of the hanger arrangement and the structural stability of a Network arch bridge – a tied-arch bridge with inclined hangers that cross each other at least twice. It is also necessary to make a comparative analysis with other types of hanger arrangements. Methodology. The authors in their research investigated a large number of parameters to determine their influence in the force distribution in the arch. Eventually they determined optimal values for all parameters. These optimal values allowed developing a design guide that leads to optimal arch design. When solving this problem, the authors used three-dimensional finite element models and the objective was to determine the most suitable solution for a road bridge, with a span of 100 meters, consisting of two inclined steel arches, located on a road with two traffic lanes, subjected to medium traffic. The virtual prototype of the model is performed by finite element simulator Midas Civil. Findings. In this study, for the bridge deck, a concrete tie appears to be the best solution considering the structural behavior of network arches, but economic advantages caused by easier erection may lead to steel or a composite bridge deck as better alternatives. Design requirements and local conditions of each particular bridge project will decide the most economic deck design.Originality. To ensure passenger comfort and the stability and continuity of the track, deformations of bridges are constricted. A network arch is a stiff structure with small deflections and therefore suitable to comply with such demands even for high speed railway traffic. A network arch bridge with a concrete tie usually saves more than half the steel required for tied arches with vertical hangers and concrete ties. Practical value. Following the study design advice given in this article leads to savings of about 60 % of structural steel compared with conventional tied arch bridges with vertical hangers.